PENGARUH MODAL INTELEKTUAL PADA KINERJA PASAR PERUSAHAAN (Studi Empiris pada Perusahaan Keuangan yang Terdaftar di Bursa Efek Indonesia) - YUNIASIH, NI WAYAN; WIRAMA, DEWA GEDE; BADERA, I DEWA NYOMAN (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 2 (2011))
Intellectual capital is believed to be a contributing factor to companies’ performances and values. Several studies have been carried out on the influence of this capital to a company’s performance. However, the results still show some inconsistencies. Therefore, this study aims at re-evaluating the influence of intellectual capital through the addition of ownership structure as a control variable. Ownership structure needs to be controlled since, in Indonesia, it is likely to be concentrated due to the low rate of investor protection. Intellectual capital is measured by the VAICTM method, while the market performance is determined by the price to book value ratio. The sample is financial companies listed on Indonesian Stock Market during the 2004-2008 periods. The result of the analysis fails to support the hypothesis that intellectual capital is associated with firm’s values. The result probably is an indication that market is incapable to assess the value of a company’s intellectual capital because it has no standardized measure and the limited quantitative disclosure regarding intellectual capital.
Keywords: intellectual capital, value added, ownership structure, market performance